Exploring the delays at empty container off-dock depots: useful perceptions by stakeholders - Rosmaizura Mohd Zain; Mohd Nizam Ab. Rahman; Nizaroyani Saibani; Zulkifli Mohd Nopiah; Ainon Ramli; Norzaliha Jusoh (2015)
To date, however, there has been little investigation into how and why bottlenecks occur at the empty container off-dock depots around the world. Therefore, we accomplished the case study at the off-dock depot which located outside the terminal of Port Klang, Malaysia. The purpose of this paper is to investigate the delays that hinder the rapid movement of empty containers in the context of bottlenecks and congestion. In particular, the paper aims to reveal the stakeholders’ perceptions and identify the main causes of the bottlenecks that exist at off-dock container depots. Based on direct observations and in-depth interviews with a panel of thirty experts in the physical movement of empty containers, the results indicated that the most frequent causes of bottlenecks that stakeholders perceived included work attitudes, operations handling, monitoring, information and facilities/others. Of these, the ‘operations handling’ related to container depots was considered the most significant identifiable barrier to container movements. The research outcomes should assist the container chain players to understand the practice requirements for empty containers in Malaysia.